CRANIOMETRIC STUDY OF MEDIEVAL CIRCASSIANS: EVIDENCE FROM GOSUDARSTVENNIY NO. 258 AND GOSTAGAEVSKAYA-1 BURIAL GROUNDS - Abramova, Aleksandra Nikolaevna (History, Archeology and Ethnography of the Caucasus, 2025)
This study presents the results of a morphometric analysis of craniological data from two series attributed to the Circassian population of the late 12th to 13th centuries, based on associated material culture. The samples originate from burial grounds located on the Right Bank of the Kuban River, designated as “Gosudarstvenniy No. 258” and “Gostagaevskaya-1.” Both burial grounds were excavated from mounds and are situated in close proximity to each other. However, differences in funerary practices were observed, notably the use of stone crepides in the mounds of “Gosudarstvenniy No. 258.” Both series exhibit significant skeletal fragmentation, limiting the analysis to seven male crania from “Gosudarstvenniy No. 258” and eight male crania from “Gostagaevskaya-1,” examined using an expanded craniometric program. The objectives of this study are to characterize the craniometric features of the two samples, compare them using Student’s t-test, and conduct an intergroup comparison with previously published data. The population associated with “Gosudarstvenniy No. 258” is characterized by a dolichocranic cranial vault and a narrow face, with most latitudinal cranial dimensions exhibiting average values. In contrast, the population from “Gostagaevskaya-1” is mesocranic and narrow-faced, with most cranial dimensions also showing average values. Both series are classified within the broader Eurasian racial group. Statistical analysis revealed significant similarities between the two samples. Intergroup comparison, employing canonical analysis, indicated a high degree of similarity with Adyghe series from the 13th to 15th centuries.